2022
DOI: 10.1038/s41467-022-28976-4
|View full text |Cite
|
Sign up to set email alerts
|

Norway spruce postglacial recolonization of Fennoscandia

Abstract: Contrasting theories exist regarding how Norway spruce (Picea abies) recolonized Fennoscandia after the last glaciation and both early Holocene establishments from western microrefugia and late Holocene colonization from the east have been postulated. Here, we show that Norway spruce was present in southern Fennoscandia as early as 14.7 ± 0.1 cal. kyr BP and that the millennia-old clonal spruce trees present today in central Sweden likely arrived with an early Holocene migration from the east. Our findings are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 63 publications
4
19
0
Order By: Relevance
“…Utilizing genomic data from almost 5000 trees sampled across Sweden and the natural range of Norway spruce, we reconstructed the origin of the contact zone separating the south and the north of Scandinavia and showed that the contact zone corresponds to a major climatic transition, and natural selection acting on gene clusters dispersed across the whole genome contributes to the maintenance of the differentiation between the two sides of the contact zone. Given that Norway spruce has been present in Scandinavia for a limited number of generations (Giesecke & Bennett, 2004;Nota et al, 2022), this is an important result with respect to climate change because, unless trees were preadapted before invading Scandinavia, it suggests rapid local adaptation. It has often been assumed that trees, because of their long generation times, will be poorly equipped to respond rapidly to climate change (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Utilizing genomic data from almost 5000 trees sampled across Sweden and the natural range of Norway spruce, we reconstructed the origin of the contact zone separating the south and the north of Scandinavia and showed that the contact zone corresponds to a major climatic transition, and natural selection acting on gene clusters dispersed across the whole genome contributes to the maintenance of the differentiation between the two sides of the contact zone. Given that Norway spruce has been present in Scandinavia for a limited number of generations (Giesecke & Bennett, 2004;Nota et al, 2022), this is an important result with respect to climate change because, unless trees were preadapted before invading Scandinavia, it suggests rapid local adaptation. It has often been assumed that trees, because of their long generation times, will be poorly equipped to respond rapidly to climate change (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The recolonization of Northern Europe by P. abies started relatively late, and spruce migration rates for Fennoscandia varied between 200 and 500 m yr −1 (Lehsten et al ., 2014 ). As for many other species, for example humans (Günther et al ., 2018 ; Peter et al ., 2020 ), aspens (De Carvalho et al ., 2010 ), brown bears (Bray et al ., 2013 ) and rodents (Jaarola et al ., 1999 ), our data support the existence of two routes of recolonization of Scandinavia, both from east to west, but one entering Scandinavia from the north and moving southward and one entering Scandinavia at a lower latitude and moving both northward and southward (Giesecke & Bennett, 2004 ; Nota et al ., 2022 ). The two routes joined between 60°N and 63°N and created an admixture zone that was identified in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palaeoecological reconstructions have shown that plants have a remarkable capacity to rapidly, i.e., on a decadal time-scale, colonize formerly glaciated areas (Nota et al, 2022), but less is known about the colonization rate of soil organisms after deglaciation or permafrost thaw. From studies of glacier forelands, where soil organisms can establish in open niches via shortrange dispersal, we know that mature soil fauna communities can establish within a century (Kaufmann et al, 2002).…”
Section: A Dispersal Constrained Community Of Soil Organisms In North...mentioning
confidence: 99%
“…Karst.) is a dominant boreal conifer species that thrives nowadays in a vast northern domain spanning from Norway to central Russia, as well as in smaller European domains, such as the Alps and the Carpathians (Vendramin et al, 2000; Tsuda et al, 2016; Li et al, 2022; Nota et al, 2022). Repeated demographic movements associated to climatic cycles and ensuing secondary contacts led to the division of Norway spruce into seven genetic clusters (Chen et al, 2019): Northern Fennoscandia (NFE), Central and South Sweden (CSE), Russia-Baltics (RBA), Northern Poland (NPL), Central Europe (CEU), Alpine (ALP), Carpathian (ROM) domains.…”
Section: Introductionmentioning
confidence: 99%